The effects of qualitatively different acute physical activity interventions in real-world settings on executive functions in preadolescent children. (October 2015) - Jäger, Katja; Schmidt, Mirko; Conzelmann, Achim; Roebers, Claudia M.
Abstract: There is growing evidence indicating a positive effect of acute physical activity on cognitive performance in children. Most of the evidence originates, however, from studies in highly controlled laboratory settings. The aim of the present study was to investigate whether the same effects can be found in more real-world settings. We examined the effects of qualitatively different acute physical activity interventions on the three core dimensions of executive functions (updating, inhibition, shifting). In an experimental between-subject design, 219 ten to twelve year-olds were assigned to one of four conditions which varied systematically in physical activation and cognitive engagement. Executive functions were measured before and immediately after the intervention. Contrary to the hypothesis, no effects of acute physical activity with and without cognitive engagement were found on executive functions in the overall sample. Only children with higher fitness and/or higher academic achievement benefitted from the interventions in terms of their updating performance. Thus, the results indicate that it may be more difficult to attain positive effects through acute physical activity in real-world settings than in laboratory settings and that physiological and cognitive requirements may have to be adjusted to individual capacity to make an intervention effective. Highlights: Qualitatively different acute physical activity interventions in a real-world setting. None of the interventions benefitted executive functions in the overall sample. Benefits only in children with higher fitness and/or higher academic achievement. Transfer of effects found in laboratory settings into praxis may be difficult. Physical and cognitive requirements may need to be adjusted to individual capacity.